1976
DOI: 10.1002/bjs.1800630113
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic pseudocysts

Abstract: Twenty-seven patients with 32 pancreatic pseudocysts have been seen during the past 10 years at St George's Hospital, London. Two of the pseudocysts were found in unusual positions--one in the right inguinal canal and the other one in the porta hepatis. Approximately half of the pseudocysts in this series followed biliary-induced pancreatitis. The various clinical presentations are reported and the surgical treatment is discussed. Internal drainage is the most effective treatment and in the majority of cases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

1978
1978
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
2
0
4
Order By: Relevance
“…Further investigations using ultrasonography and pancreatography have shown that 6-23 per cent of these cysts are multiple (Anderson, 1972;Sankaran and Walt, 1975;Duncan et al, 1976). The diagnosis of a pancreatic pseudocyst is usually based on a history of acute pancreatitis in association with an abdominal mass (Becker et al, 1968); however, an abdominal mass is only found in about half of the cases (Warren et al, 1966;Becker et al, 1968;Sankaran and Walt, 1975;Grace and Jordan, 1976;Karatzas, 1976). Abdominal pain is always present, but the severity can vary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigations using ultrasonography and pancreatography have shown that 6-23 per cent of these cysts are multiple (Anderson, 1972;Sankaran and Walt, 1975;Duncan et al, 1976). The diagnosis of a pancreatic pseudocyst is usually based on a history of acute pancreatitis in association with an abdominal mass (Becker et al, 1968); however, an abdominal mass is only found in about half of the cases (Warren et al, 1966;Becker et al, 1968;Sankaran and Walt, 1975;Grace and Jordan, 1976;Karatzas, 1976). Abdominal pain is always present, but the severity can vary.…”
Section: Discussionmentioning
confidence: 99%
“…The serum amylase is moderately elevated in 33-78 per cent of patients with a pancreatic pseudocyst (Warren et al, 1966;Becker et al, 1968;Sankaran and Walt, 1975;Grace and Jordan, 1976;Karatzas, 1976). Salt and Schenker (1976), in a review of the clinical significance of the serum amylase, found hyperamylasaemia in a large number of unrelated abdominal conditions, indicating that a raised serum amylase level in association with abdominal pain is probably of limited clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Μικρές ψευδοκύστεις μπορεί να είναι ασυμπτωματικές. Τα συχνότερα συμπτώματα με τα οποία εμφανίζονται είναι: δυσφορία και αίσθημα βάρους στην άνω κοιλία [76,132,152,445,562], επιγαστρικό άλγος [76,132,445,582] (ποσοστό 70-93% [24,36,117,165,276,339,392,434,479,487,562]), ναυτία και έμετος [152,165] (ποσοστό 40-65% [36,117,276,339,392,487,562]), διαταραχές της κινητικότητας του πεπτικού σωλήνα [582] (δυσπεπτικά φαινόμενα [76,445], διάρροια [276,339,445,487,582], αίσθημα ταχείας πλήρωσης του στομάχου [445]), ανορεξία [152,175,282], μη ανοχή ποικιλίας τροφών [445], απώλεια βάρους (25-59%) [36,276,339,…”
Section: κλινική εικόναunclassified
“…Γενικά, η εξωτερική παροχέτευση προτιμάται σε κύστεις με "ανώριμο" τοίχωμα, φλεγμαίνουσες, αιμορραγούσες ή ραγείσες, που δεν επικοινω νούν με τον μππ [76], και σε ασθενείς επιβαρυμένους [27,76,117,152,276,412,516,612]. Εχει ικανοποιητικά αποτελέσματα στο 60-65% των Ά περιπτώσεων που εφαρμόζεται [76,411].…”
Section: παροχέτευση με σωλήναunclassified
See 1 more Smart Citation